Nonconservative current-induced forces: A physical interpretation - Todorov, Tchavdar N.; Dundas, Daniel; Paxton, Anthony T.; Horsfield, Andrew P. (Beilstein Journal of Nanotechnology, 2011)
We give a physical interpretation of the recently demonstrated nonconservative nature of interatomic forces in current-carrying nanostructures. We start from the analytical expression for the curl of these forces, and evaluate it for a point defect in a current-carrying system. We obtain a general definition of the capacity of electrical current flow to exert a nonconservative force, and thus do net work around closed paths, by a formal noninvasive test procedure. Second, we show that the gain in atomic kinetic energy over time, generated by nonconservative current-induced forces, is equivalent to the uncompensated stimulated emission of directional phonons. This connection with electron–phonon interactions quantifies explicitly the intuitive notion that nonconservative forces work by angular momentum transfer.
Keywords: atomic-scale conductors; current-induced forces; failure mechanisms; nanomotors